Causal Factors and Decision-Making Processes of Individuals as Waria in X Village, Jember Regency - Andini Shinta; Nabila, Balqis; Humairoh, Nabila; Ryani, Zakia (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The concept of sex and the concept of gender have differences that need to be understood by society. In this life, there is a phenomenon of gender identity deviation. One of the deviations of gender identity in society is in the form of the existence of transvestites. Waria is not only a change in gender expression and sexual orientation in the form of homosexuality. Of course transvestites are opposed in society socially, culturally and religiously. However, there are still individuals who choose and decide to become transgender. The act of deciding and choosing to become a transvestite is not easy. There are many risks, challenges, pressures, and conflicts within the self, family, and environment. It is interesting to study from various challenges and views on transgender, there are individuals who decide to become transgender related to the causal factors and decision-making process as transgender. the aim is to find out the causal factors and decision process as transgender. This research design applies descriptive qualitative phenomenology. The research location was conducted in X Village, Jember Regency. The research sample was collected through snowball sampling technique. The results show that individuals who decide to become transgender have contributing factors ranging from psychological conditions, parenting, and trauma from sexual violence. Furthermore, individuals go through stages that shape themselves as transgender, starting from assessing challenges, surveying alternatives, considering alternatives, commitment, and surviving through negative responses related to their decision to become transgender.